Trustworthiness, responsibility, and virtue - Hills, A (Oxford University Press, 2023)
In the current philosophical literature on trustworthiness, two claims are very widely accepted, first that trustworthiness is a kind of reliability and secondly, that trustworthiness is not a virtue. Both claims are made, for instance, in Hawley’s recent highly influential account of trustworthiness. I argue that both are mistaken. I develop and defend a new account of trustworthiness as responsibility, contrasting it with reliability and obligation accounts of trustworthiness. I argue that trustworthiness as responsibility is very plausibly a kind of moral virtue.